Evaluation of serum immunoglobulin (IgG, IgM, IgA) in oral cancer patients - A case control study - Vivek M Tarsariya; Nilesh Raval; Dhaval N Mehta; Mukesh K Asrani; Vijay K Asrani; Kaushik S Barot (Wolters Kluwer Medknow Publications, 2021)
Background: Very few studies have been done to evaluate the level of serum immunoglobulins (IgG, IgM, and IgA) in patients with oral cancer as tumor markers. Aims and Objectives: The aim of this study was to estimate the serum immunoglobulins level (IgG, IgM, and IgA) in oral cancer patients and its comparison with control groups and whether these values can be used to predict the severity of disease or not. Materials and Methods: A total of 30 patients with different clinical stages oral cancer and 30 healthy controls were selected at random and subjected for analysis of serum IgG, IgA, and IgM. Statistical methods used were the mean, standard deviation and t test. Results: Significantly elevated levels of all the immunoglobulins was observed in oral cancer patients when compared with the control group and levels were increasing with clinical stages (P < 0.05). Conclusion: All these immunoglobulins are indicative of tumor burden or transformation of malignancy in higher stage and might be used as prognostic indicators in oral cancer.